2019
DOI: 10.1021/acssensors.9b01073
|View full text |Cite
|
Sign up to set email alerts
|

Au39Rh61 Alloy Nanocrystal-Decorated W18O49 for Enhanced Detection of n-Butanol

Abstract: Here, Au x Rh1–x alloy nanocrystals (NCs) were used to decorate W18O49 for enhanced detection of n-butanol vapor. Monodisperse Au x Rh1–x alloy NCs with a tunable composition and urchinlike W18O49 were synthesized by a simple solvothermal method. Au x Rh1–x alloy NCs were loaded onto the W18O49 surface by the impregnation method. A series of material characterization methods were employed to characterize the structure and morphology of as-synthesized materials. The performance of Au x Rh1–x –W18O49-based se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Loading with a catalytically active metal nanoparticle (NP) catalyst is one of the most used methods to improve the performances for RT sensing. ,, However, metal NPs usually have relatively low catalytic activity at ambient conditions. Meanwhile, many factors, such as different crystal facets of metal NPs, synergetic effect from neighboring metal atoms, and inhomogeneous distribution of different metal atoms in alloy NPs, , would result in multiple catalytically active sites, which can simultaneously activate various analytes and degrade their selectivity. At present, the sensitivity and selectivity of metal NP catalyst-loaded MOs at RT are still unsatisfactory.…”
mentioning
confidence: 99%
“…Loading with a catalytically active metal nanoparticle (NP) catalyst is one of the most used methods to improve the performances for RT sensing. ,, However, metal NPs usually have relatively low catalytic activity at ambient conditions. Meanwhile, many factors, such as different crystal facets of metal NPs, synergetic effect from neighboring metal atoms, and inhomogeneous distribution of different metal atoms in alloy NPs, , would result in multiple catalytically active sites, which can simultaneously activate various analytes and degrade their selectivity. At present, the sensitivity and selectivity of metal NP catalyst-loaded MOs at RT are still unsatisfactory.…”
mentioning
confidence: 99%
“…The O 1s peaks of pristine NiO and In 2 O 3 -NiO (S1, S2, S3) samples are shown in Figure d. The three oxygen components are fitted from the O 1s peak, representing different states of the surface oxygen, which are the lattice oxygen (O L ), the vacancy oxygen (O V ), and the chemisorption oxygen (O C ) . It can be found that the proportions of O C of the pristine NiO and In 2 O 3 -NiO (S1, S2, S3) samples are 9.4, 11.4, 14.3, and 10.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…decorated MOSs always exhibit unique properties in the gas sensor eld owing to their specic chemical and electronic sensitization properties. 2,[10][11][12][13][14] Unfortunately, the scarcity and expense of metal catalysts greatly hinder their widespread application. Therefore, signicant strategies, such as construction of bimetals and crystal phases, crystal plane adjustment of metal catalysts, etc., have been used to construct highly active metal catalysts by increasing the number of active sites or optimizing the intrinsic activity.…”
Section: Introductionmentioning
confidence: 99%